The correct gender of Schinus (Anacardiaceae) - Zona, Scott (Phytotaxa, 2015)
Species of the genus Schinus Linnaeus (1753) (Anacardiaceae) are native to the Americas but are found in many tropical and subtropical parts of the world, where they are cultivated as ornamentals or crops (“pink peppercorns”) or they are invasive weeds.  Schinus molle L. (1753: 388) is a cultivated ornamental tree in Australia, California, Mexico, the Canary Islands, the Mediterranean, and elsewhere (US Forest Service 2015). In Hawaii, Florida, South Africa, Mascarene Islands, and Australia, Schinus terebinthifolia Raddi (1820: 399) is an aggressively invasive pest plant, costing governments millions of dollars in damages and control (Ferriter 1997).